2015
DOI: 10.1136/bcr-2015-211971
|View full text |Cite
|
Sign up to set email alerts
|

Retinal artery vasculitis secondary to administration of influenza vaccine

Abstract: There are many differential diagnoses in investigating patients who present with retinal vasculitis, and the laboratory investigations used to investigate this have low-to-moderate sensitivity and/or specificity. Diagnoses include conditions such as tuberculosis or sarcoidosis, which may require long courses of antibiotics or immunosuppression. Influenza vaccination has been recognised as a cause of vasculitis for decades, although a purely ocular presentation is rare. We present a case of a 78-year-old Caucas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
1
11
0
1
Order By: Relevance
“… 2 , 17 More recently Williams described a case of anterior uveitis and retinal arterial vasculitis 8 weeks following routine annual inactivated influenza immunization. 5 The influenza vaccine reported in this instance was similar to the one our patient received. Both cases from Blumberg et al and Williams et al reported no recurrences of uveitis or retinal vasculitis following topical 1% prednisolone treatment.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“… 2 , 17 More recently Williams described a case of anterior uveitis and retinal arterial vasculitis 8 weeks following routine annual inactivated influenza immunization. 5 The influenza vaccine reported in this instance was similar to the one our patient received. Both cases from Blumberg et al and Williams et al reported no recurrences of uveitis or retinal vasculitis following topical 1% prednisolone treatment.…”
Section: Discussionsupporting
confidence: 65%
“… 2 , 8 , 11 , 12 , 17 Ocular involvement is extremely rare and to our knowledge there are only 2 reported cases of isolated ocular complications following influenza vaccination. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear if the reported retinal vascular events in our study are specific side effects of COVID-19 vaccinations. Ocular side effects, such as retinal vascular occlusions, AMN, and anterior and posterior uveitis, were also observed after vaccination for other diseases, such as influenza or hepatitis B [15,18,19]. Reports on ocular side effects after COVID-19 vaccinations are rare so far [20].…”
Section: Discussionmentioning
confidence: 99%
“…published the case of a 78-year-old Caucasian woman who presented with a single unilateral arterial vasculitis 8 weeks after influenza vaccination. [ 91 ] Uveitis and optic neuritis were reported in one case by Blumberg et al . [ 92 ] Recrudescence of a previously quiet inflammation was reported in a 77-year old female after influenza immunization, suggesting that such a vaccine might not only trigger de novo inflammatory processes but also exacerbate pre-existing inflammation.…”
Section: Vaccines Induce Uveitismentioning
confidence: 99%